Physiological factors which influence the performance potential of athletes:Analysis of sports medicine performance testing in Nordic combined - Schupfner, Rupert; Pecher, Stefan; Pfeifer, Eva; Stumpf, Christian (The physician and sportsmedicine, 2020)
Objectives: The sports medicine performance diagnostics include investigative procedures that supply information on the performance capacity and stamina of an athlete. This creates a foundation for a personalised training plan and enables optimised control of the training process. Methods: The study population consisted of 24 male Nordic combined athletes from the national German squad. They were monitored using sports medicine testing over a period of five winter seasons. The test speeds on the treadmill in m/s are determined at lactate values of 2, 3 and 4 mmol/l in the peripheral blood values to calculate the lactate curve. Dickhuth’s model was used to determine the individual anaerobic threshold. A spiroergometric system was used to determine the maximal oxygen uptake and the VO2max in ml/(kg x min) was found. Spearman rank correlation analyses and multiple linear regression analyses were primarily used as statistical procedures. Results: The higher the test performance expressed as a percentage, the more likely it was that a top position could be achieved. The individual anaerobic threshold and the maximal oxygen uptake increased significantly with an increase in test performance expressed as a percentage. The higher the individual anaerobic threshold of the Nordic combined athlete was, the higher the placements they were able to achieve. The maximal oxygen capacity and the individual anaerobic threshold showed a positive correlation with each other: when the IAT increased, the VO2max also increased. The maximal oxygen uptake had a weak positive association with improved placement in the cross-country competitions and in the overall world cup. The older the athlete, the better they performed in the overall world cup. When age increased, the test speed [m/s] at lactate values of 2, 3 and 4 mmol/l also increased, along with the test performance expressed as a percentage, the maximal oxygen uptake and the individual anaerobic threshold. A higher BMI proved advantageous in terms of placement in the individual competitions. The lactate values on the ski rollers showed barely significant associations with the results of the athletic competitions. With regard to simplifying the performance diagnostics, the lactate performance test on ski rollers would be the easiest to dispense with. Conclusion: In this study, test speed on the treadmill [m/s] at a lactate concentration of 4 mmol/l showed the strongest influence that was independent of other parameters on the sporting performance of the Nordic combined athletes. Regardless of how the lactate threshold is determined, a lactate value of 4 mmol/l should almost always be above an indicative anaerobic threshold, meaning that the application of this parameter is more valid than using an arbitrary individual threshold, both physiologically and mathematically. In this vein, the test speed at a lactate concentration of 4 mmol/l can be recommended as a robuster, more independent from mathematical models and physiologically more valid parameter for performance diagnostics in professional athletes and was independent of other parameters.
CRIS-Team Scopus Importer:2024-12-04